2021
DOI: 10.3389/fpsyg.2021.662639
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Literacy and Communicative Skills of Students With Disabilities in Special Schools Through Dialogic Literary Gatherings

Abstract: Enhancing the quality of learning opportunities for students with disabilities and the learning level attained is a pending challenge. This challenge is especially relevant in the context of special schools, where the learning possibilities derived from interactions with others is limited. However, providing these students with a sufficient level of instrumental learning, such as literacy, and communicative and reasoning abilities is crucial for their subsequent educational and social opportunities. In this ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Most research (Fernández-Villardón, Valls-Carol, Melgar Alcantud, & Tellado, 2021;Ritter, Gu, Crijns, & Biekens, 2020) concurs that universities need to foster students' creative abilities. However, there is no proper definition of creativity in education (Perry & Collier, 2018;Sidek, Halim, & Buang, 2022) and academic institutions have not established methods for measuring its development or tools specifically designed to monitor student progress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most research (Fernández-Villardón, Valls-Carol, Melgar Alcantud, & Tellado, 2021;Ritter, Gu, Crijns, & Biekens, 2020) concurs that universities need to foster students' creative abilities. However, there is no proper definition of creativity in education (Perry & Collier, 2018;Sidek, Halim, & Buang, 2022) and academic institutions have not established methods for measuring its development or tools specifically designed to monitor student progress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of early childhood education, DLGs are increasingly being applied in new contexts (European Commission, 2019). Their implementation has been documented in countries such as the United Kingdom, Spain and Portugal and in different Latin American countries, including Brazil, Colombia and Mexico (European Union, 2019;General Directorate of Education, 2021;Rodríguez-Oramas et al, 2021). However, little research analyses DLGs in early childhood education in depth (Soler-Gallart & Flecha, 2018).…”
Section: Dlgsmentioning
confidence: 99%
“…DLGs have been widely analysed and shown to promote high‐quality instructional, emotional and social interactions in adult and primary education (Fernández‐Villardón et al, 2021; Soler, 2015). Previous research has also found that DLGs can promote prosocial behaviour, better integration of students with disabilities and social inclusion of vulnerable groups in primary education (Molina, 2015; Villardón‐Gallego et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…DLGs consist of choosing a book from among the classics of world literature, agreeing among participants which chapters to read, reading what has been agreed upon and underlining the sentences that are considered interesting, and then getting together to read and comment on the paragraphs that have been underlined (Fernández-Villardón et al, 2021 ). The role of the moderator is not to lecture on the analysis of the book but to ensure that mutual respect and interest prevail and that everyone feels comfortable and legitimated to participate and thus enrich the conversation (García et al, 2017 b).…”
Section: Introductionmentioning
confidence: 99%